Does competent bilingualism entail advantages for the third language learning of immigrant students?. (December 2018) - Edele, Aileen; Kempert, Sebastian; Schotte, Kristin
Abstract: This study examined the role of immigrant bilingualism in third language learning (L3 = English). It focused on the respective effects of students' competence in the minority language (L1 = Turkish or Russian) and language of instruction (L2 = German). We analyzed a sample of 8752 German 10 th -grade students ( N = 7964 monolinguals, N = 436 Turkish-German students, N = 352 Russian-German students) and drew on standardized tests in L1, L2, and L3. OLS-regression models showed L3 advantages for balanced bilinguals at a high level in both language groups compared to their average monolingual peers when third variables were controlled, while advantages in the L2 dominant bilinguals could only be observed in the Russian-German sample. Balanced bilinguals at a low level and L1 dominants attained lower L3 levels than monolinguals. However, comparisons with comparably high proficient monolinguals, as well as further analyses with the bilingual samples separately, revealed that only L2 competence – and not L1 competence – explained immigrant students' L3 proficiency. Our findings indicate that the advantages of immigrant bilinguals in L3 learning mainly depend on their competence in the language of instruction. Highlights: No L3 advantages for immigrant bilingual students with different language profiles compared to monolinguals with similar levels of L2 proficiency. Immigrant bilingual students' L3 proficiency is related to L2 proficiency rather than to L1 proficiency. Immigrant students' competence in the language of instruction appears to be pivotal for L3 learning.